Preparation, immunological and pharmacological effects of flavonoids in Scutellariae radix: a review - Chen, Haixia; Wei, Yumin; Song, Jing; Yang, Yue; Chen, Yanli; Sun, Jiteng; Bai, Daoming; Sun, Zhiqiang; Wu, Mingze; Liu, Xiaomei; Lin, Yanru; Wang, Shaoping; et al. (Frontiers in Pharmacology, 2026)
In traditional Chinese medicine theory, Scutellaria baicalensis Georgi [Lamiaceae; Scutellariae radix] (SR) is bitter and cold in nature. It enters the lung, gallbladder, spleen, large intestine, and small intestine meridians. It clears heat and dries dampness, purges fire and detoxifies, stops bleeding, and stabilizes pregnancy. It excels at clearing lung fire and upper-body heat. Flavonoids, the primary active compound of SR, undergo metabolism in vivo through Phase I and Phase II reactions as well as intestinal flora-mediated processes. Modern pharmacological research indicates that flavonoid compounds exhibit diverse biological activities in immune modulation, antiviral, anti-inflammatory, antibacterial, and antitumor effects. In recent years, novel formulations such as nanomedicines and liposomes have garnered increasing attention to enhance their stability and bioavailability. This review systematically summarizes the research progress on flavonoid compounds in SR, comprehensively elaborating on their phytochemistry, extraction methods, separation and purification techniques, in vivo metabolism, immunological and pharmacological effects, toxicity, and novel dosage forms. It provides theoretical foundations and practical references for the further research, development, and rational application of these compounds.